STRENGTHENING STUDENT WELL-BEING: THE ROLE OF MENTAL HEALTH EDUCATION IN CO-EDUCATIONAL SETTINGS - Zhang , Lei Feng; Hong, Liu Xiao (Research Journal of Education and Allied Studies, 2024)
In the process of students' psychological development, addressing their inner contradictions and conflicts is crucial to prevent mental health problems. This article focuses on the importance of mental health education, utilizing psychological theories and educational methods tailored to students' growth stages. By nurturing psychological resilience and emotional well-being, this approach aims to eliminate negative psychological experiences, fostering a holistic development that harmonizes both physical and psychological aspects. The family-school co-education model, which involves a collaborative effort between schools and parents in guiding children's growth, plays a pivotal role in this context. It not only influences students' learning but also has a significant impact on their mental health. To integrate mental health education effectively within the family-school co-education framework, teachers must employ scientific teaching methods to enhance students' psychological resilience. This approach results in more well-rounded development and improved educational outcomes.